TRANSFORMASI STRUKTUR EKONOMI NASIONAL INDONESIA: PILAR STRATEGIS MENUJU PEMBANGUNAN BERKELANJUTAN DAN KESEJAHTERAAN MASYARAKAT - Sumanti; Ria Pratiwi; Tri Wahyuni; Ramajenur Anas; Dinni Widya Putri; Satria Angraini Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The national economic structure reflects the composition and interconnection of economic sectors that determine a country’s development direction and welfare level. Indonesia, as a developing country with abundant natural resources and a large population, continues to face challenges in transforming its economic structure from a primary-sector-based economy toward a more productive industrial and service-oriented economy. This article aims to analyze the concept of the national economic structure, the role of economic institutions, market mechanisms, and economic sectors in supporting sustainable national development. This study employs a literature review method by examining books, official reports, and recent academic sources relevant to national economic development. The findings indicate that a balanced and integrated economic structure strengthens economic resilience, encourages inclusive growth, expands employment opportunities, and enhances national competitiveness. Structural transformation supported by effective policies, strong institutions, and human resource development is crucial to achieving equitable and sustainable economic growth. Therefore, strengthening the national economic structure is a strategic necessity for Indonesia in responding to global economic dynamics.